2017
DOI: 10.1111/liv.13411
|View full text |Cite
|
Sign up to set email alerts
|

UGT1A polymorphisms as genetic biomarkers for hepatocellular carcinoma risk in Caucasian population

Abstract: A predictive effect of UGT1A polymorphisms on HCC risk was identified. If confirmed, these findings could contribute to improve the HCC surveillance, treatment tailoring and patients care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The ethnicity of the population being studied is a crucial factor in case-control studies, because polymorphism frequency varies greatly with geographical origin. This association could give rise to ethnicity-specific phenotypic effects[ 4 , 14 ]. The present study revealed some novel genetic markers that could be used as early diagnosis indicators for liver cancer susceptibility in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ethnicity of the population being studied is a crucial factor in case-control studies, because polymorphism frequency varies greatly with geographical origin. This association could give rise to ethnicity-specific phenotypic effects[ 4 , 14 ]. The present study revealed some novel genetic markers that could be used as early diagnosis indicators for liver cancer susceptibility in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…The CART analysis generated a distinctive clustering of subjects, according to different probabilities of developing liver cancer. These data pointed out that previously acknowledged predictive markers, such as the UGT1A*3 polymorphism[ 14 ], should be considered in association with novel identified genetic variants for properly defining the complex trait of HCC susceptibility. In particular, ERCC1 rs3212986 was shown to be the most relevant polymorphism for HCC risk stratification, because it appeared twice in the generated tree.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The last episode in the search for the dangerous liaisons between UGT1A and HCC has been published recently in Liver International. 15 In this work, de Mattia and coworkers conducted a case-control study on patients transplanted for HCC (cases, n=192), and on two sets of controls, the first set composed of patients chronically infected with hepatitis B or C viruses and the second set composed of healthy blood donors. The authors looked for the presence of six polymorphisms located in UGT1A1 (n=3), UGT1A7 (n=2) and UGT1A9 (n=1).…”
Section: Editorialmentioning
confidence: 99%